COMPARING QUESTIONNAIRE RESULTS AND LEARNING OUTCOMES IN CLINICAL LABORATORY TRAINING PROGRAMS TO SUPPORT LEARNING IN JAPAN - Goto, Kazuo (Asian Journal Of Medical Technology, 2022)
In Japan, the Ministry of Education, Culture, Sports, Science, and Technology requires every university to complete a learning behavior survey, assess the results, and disclose this information as part of the university's evaluation. This study examines the correlation between the results of the analysis conducted in a university for medical technologists and their learning outcomes, including GPA, graduation exam scores, and national exam scores. The learning behavior survey conducted in March 2020 included 345 participants studying medical technology. In total, 20 items were categorized based on seven factors. The results for the senior students were collated with their GPA scores, graduation exam scores, and national examination scores through factor analysis and multiple regression analysis using their scores and the factor scores. The results revealed that as students advance to upper grades, their efforts toward studying, such as study time, increase; however, no simple correlation exists between the increased study time and the resulting achievement. The medical technologist national exam scores were found to have a strong, positive correlation to three factors: effective use of leisure time, living environment, and observance of deadlines. The learning behavior survey analysis offers suggestions for students on the actions they must take to pass the national medical technologist exam.